Preheating ventilating air with solar energy - C K Spillman; F V Robbins; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1976)
When animals are confined inside buildings, ventilating air is required to remove moisture and odors. Young animals require relatively warm temperatures and do not produce enough heat to offset that lost through walls and to warm ventilating air. Supplemental heat required by young animals does not need to be high quality, and heating the air a few degrees is adequate for much of the fall, winter, and spring. For example, assume that a 26-sow, farrowing house has a 500 cfm fan. Current recommendations are to run that size fan continuously during the winter. If the ventilating air is heated 30 degrees, it requires 16,000 Btu per hour or 1 gallon of LP gas every 4.3 hours.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Ventilating air; Heating; Farrowing